Quzhuo tongbi formula for reducing gout flare related to uric acid lowering treatment: Study protocol for a multiple-center, randomized, double-blind, placebo, parallel-controlled clinical trial - Pan, Hejing; Li, Xuanlin; Wu, Shan; Zhou, Donghai; Guan, Haojie; Wu, Haoyu; Wang, Qiao; Tang, Yujun; Hu, Xuanming; Wang, Meijiao; Zhou, Mingqian; Huang, Runyue; et al. (PloS one, 2025)
Gout, a prevalent metabolic rheumatic disease, arises from the accumulation of monosodium urate (MSU) crystals in joints, directly associated with hyperuricemia. Long-term or lifelong urate-lowering therapy (ULT) stands as the primary management strategy. However, there is a significant risk of gout flares during ULT, and current methods have drawbacks, including side effects. Previous research has suggested a potential benefit of the Qu-zhuo Tong-bi formula (QTF) in the treatment and prevention of gout. This study aims to evaluate the effectiveness and safety of QTF in reducing gout flares during ULT. This is a multi-center, randomized, double-blind, placebo, parallel-controlled clinical trial conducted in four hospitals in Zhejiang Province, China. A total of 144 patients, aged 18-80 years, will be randomly allocated to either the intervention group (QTF + febuxostat) or the control group (placebo + febuxostat) for a 12-week treatment period. The primary outcome measure is the frequency of gout flares. Secondary outcome measures include the time from the patient's enrollment to the first occurrence of gout flare (in days), duration of gout flare (in days), health assessment questionnaire disability index (HAQ-DI), pain level (visual analog scale - VAS), rate of achieving target uric acid levels. Occurrences of adverse events, and results from electrocardiograms and laboratory tests, will be monitored. The findings from this study will offer valuable evidence supporting the efficacy of the QTF in reducing gout flares during ULT. ChiCTR20084417 Register on May 16, 2024.